Legal Consequences Of Land Nominee Agreements Related To Foreign Ownership (Decision Analysis Of Gianyar State Court Number 259/Pdt.G/2020/Pn.Gin) - Khairunnisa Khairunnisa; Mohamad Fajri Mekka Putra (Fakultas Hukum, Universitas Islam Bandung, 2022)
Under the Basic Agrarian Law No. 5 of 1960 article 21 paragraph 1 stated that only Indonesia citizen may have the right of ownership and it is the main principle of right of ownership in Indonesia. However, it would not be a problem for foreign citizen to have the right of land ownership in Indonesia with the use of Nominee Agreement. Nominee agreement is a form of legal smuggling towards the right of ownership by foreign citizen. The research method that will be used in this article is a juridical-normative approach by using primary and secondary legal material. As for the approach that will be used is the study documents through library research derived from statutes, publications, and related legal articles. The result shows the use of nominee agreement in right of ownership towards foreign citizen is null and void. The legality of this agreement is dubious because it does not fulfill the requirements for the validity of agreements, that is a legal cause. There is no legal protection towards the notary who create this agreement.